2020
DOI: 10.1080/16549716.2020.1765526
|View full text |Cite
|
Sign up to set email alerts
|

Assessing completeness of patient medical records of surgical and obstetric patients in Northern Tanzania

Abstract: Background: Strengthening surgical services in resource-constrained settings is contingent on using high-quality data to inform decision making at clinical, facility, and policy levels. However, the evidence is sparse on gaps in paper-based medical record quality for surgical and obstetric patients in low-resource settings. Objective: We aim to examine surgical and obstetric patient medical record data quality in health facilities as part of a surgical system strengthening initiative in northern Tanzania. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…In addition to missing medical records, the findings showed that primary data quality is weak in health care facilities in northern Tanzania. 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to missing medical records, the findings showed that primary data quality is weak in health care facilities in northern Tanzania. 35…”
Section: Resultsmentioning
confidence: 99%
“…In addition to missing medical records, the findings showed that primary data quality is weak in health care facilities in northern Tanzania. 35 Table 2 The most common data quality dimensions and their definitions…”
Section: Data Quality In Paper-based Medical Recordsmentioning
confidence: 99%
“…Pre-intervention, maternal sepsis, postoperative sepsis and SSI were poorly documented in patient records [ 29 ]. After intervention, documentation of sepsis and SSI diagnosis and care improved.…”
Section: Discussionmentioning
confidence: 99%
“…Missing patient records is also a problem, as in Tanzania, where a study surveying the completeness of records found 32% missing. 32 HRR studies often carry systematic biases and only provide institutional MMRs. As institutions only serve selected populations, health records represent selected population groups, e.g.…”
Section: Health Record Review Studiesmentioning
confidence: 99%